Geography and the evolution of rural nonfarm sector in the Philippines, 1988-2006 - Estudillo, Jonna P.; Ramos, Charity Gay; Otsuka, Keijiro (The Philippine Review of Economics, 2009)
This paper aims to assess the changing impact of distance on the development of rural labor force between the farm and nonfarm sectors in the Philippines using provincial-level data from 1988 to 2006. The impact of distance of a province from a major city on the growth impact of its rural nonfarm sector did not change over time because of the concentration of infrastructure developments in provinces located in major cities.